Behaviors and effects of Zn coating on welding-brazing process of Al-Steel and Mg-steel dissimilar metals. (January 2018) - Cao, R.; Chang, J.H.; Huang, Q.; Zhang, X.B.; Yan, Y.J.; Chen, J.H.
Abstract: The behaviors and effects of Zn-coating on the welding-brazing processes of steel with aluminum and magnesium were investigated by Cold Metal Transfer (CMT) arc. The behaviors of Zn-coating at the very beginning of burning and during the spreading of the liquid aluminum and liquid magnesium droplet over the steel plate were observed respectively. The effects of Zn-coating on the wetting process of liquid droplets and on the fracture of welding-brazing joints were analyzed. The effects of Zn-coating on joining mechanisms and tensile load of Al-steel joints and Mg-steel joint were compared and analyzed. For Al-steel, Mg-steel, some common behaviors can be found, the main effect of Zn is its evaporation which decreases the temperature at the interface to prevent steel from melting and makes the steel to expose the fresh metallic surface which is much easier to be spread by a liquid droplet than an oxidized surface. Zn-coating improves the wettability of liquid Al or liquid Mg over the steel surface. However, some effects of zinc coating on wetting behavior, joining mechanisms and tensile load of Al-steel joints and Mg-steel joint are still different. For Al-steel arc, Zn-rich triangle zone is not formed by driving the liquid Zn from inside and accumulated at the toe, rather it is formed by the diffusion of the liquid Zn from outside Zn-enriched periphery into the droplet. In the case of Mg-steel arc, the Zn-rich zone forms partly due to the accumulation of Zn driven from the center during the Zn evaporation. For Al-steel joint, Zinc coating has not reacted to form the interface layer between Al weld metal and steel, however, zinc coating reacted to form the interface layer between Mg weld metal and steel. Zinc coating improved the strength of Al-steel joints, but, it is not beneficial to the strength of Mg-steel joint.